2013
DOI: 10.1063/1.4812469
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecule recognition using piezoresistive nanomechanical force probes

Abstract: Highly sensitive sensors are one of the enabling technologies for the biomarker detection in early stage diagnosis of pathologies. We have developed a self-sensing nanomechanical force probe able for detecting the unbinding of single couples of biomolecular partners in nearly physiological conditions. The embedding of a piezoresistive transducer into a nanomechanical cantilever enabled high force measurement capability with sub 10-pN resolution. Here, we present the design, microfabrication, optimization, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…It is well-known that a reduction in cantilever size increases both sensitivity and detection speed 7 8 , and this diffraction limit presents a major barrier for the use of OBD readout with increasingly miniaturized cantilevers. Beyond the OBD technique, many other deflection sensing techniques were proposed in the past: capacitive 9 10 11 12 13 , doped silicon and polysilicon piezoresistive 14 15 16 17 18 19 20 21 22 , piezoelectric 23 24 25 26 , magnetic 27 28 and thin metal film 7 29 30 deflection sensing. Techniques with strain-sensing elements incorporated in the cantilever are of a particular interest, offering several advantages over external readout techniques 31 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that a reduction in cantilever size increases both sensitivity and detection speed 7 8 , and this diffraction limit presents a major barrier for the use of OBD readout with increasingly miniaturized cantilevers. Beyond the OBD technique, many other deflection sensing techniques were proposed in the past: capacitive 9 10 11 12 13 , doped silicon and polysilicon piezoresistive 14 15 16 17 18 19 20 21 22 , piezoelectric 23 24 25 26 , magnetic 27 28 and thin metal film 7 29 30 deflection sensing. Techniques with strain-sensing elements incorporated in the cantilever are of a particular interest, offering several advantages over external readout techniques 31 .…”
mentioning
confidence: 99%
“…Initial piezoresistive self-sensing cantilevers primarily used doped silicon resistors 14 15 17 19 20 21 22 , followed by cantilevers with polysilicon 32 33 34 35 and thin metal film 7 29 30 strain-sensing resistors. Piezoresistors measure strain through a change in resistivity (effect dominant in semiconductors) and a change in geometry (effect dominant in metals).…”
mentioning
confidence: 99%
“…For cantilevers with 250 lm length, 2 lm leg width (total width 8 lm) and a thickness of 465 nm on the piezoresistor and 325 nm elsewhere, they achieved a force sensitivity of 158 lV/nN, a noise of 5.9 lV (1 Hz-1 kHz) and a minimum detectable force of 37 pN with a relative standard deviation of 8% over 24 devices [49]. With further fabrication process optimisation, Tosolini et al showed an improved resolution of 9 ± 3 pN (or 14 ± 4 nm) for the 1 Hz-10 kHz bandwidth [43]. These cantilevers were used to demonstrate the AFS detection in liquid of specific biorecognition events in the avidin-biotin complex (Fig.…”
Section: Nanomechanical Sensors For Physical and (Bio)chemical Measurmentioning
confidence: 94%
“…These cantilevers were used to demonstrate the AFS detection in liquid of specific biorecognition events in the avidin-biotin complex (Fig. 6d), with an experimental unbinding force of 44 ± 12 pN [43].…”
Section: Nanomechanical Sensors For Physical and (Bio)chemical Measurmentioning
confidence: 99%
See 1 more Smart Citation